Greater male variability in creativity: A latent variables approach. (December 2016) - Karwowski, Maciej; Jankowska, Dorota M.; Gralewski, Jacek; Gajda, Aleksandra; Wiśniewska, Ewa; Lebuda, Izabela
Highlights: Gender variability in creativity hypothesis is tested. Both cross-sequential and cross-sectional studies confirm the greater male variability (GMVH). The GMVH was visible as early, as among 4 year old children. Abstract: Although gender differences do not usually exist when it comes to creative potential, males do exhibit a higher variability of creative ability: the effect that may result in more males than females having both very low and very high creative potential. Two studies examined the greater male variability in creativity hypothesis (GMVC): a cross-sequential investigation conducted on a sample of children (4–7 years old; N  = 351) over the span of two years and a cross-sectional study conducted on a sample diverse in age (6–46 years old; N  = 3594). In both studies, the Test of Creative Thinking-Drawing Production (TCT-DP; Urban & Jellen, 1996) was used, but unlike previous research, data were analyzed using the latent variables approach: latent growth curve modeling (Study 1) and exploratory and confirmatory factor analyses (Study 2). Greater male variability of creative ability was found across studies and age groups, but while this pattern was characteristic for some aspects of creative ability (originality and unconventionality), higher female variability was observed in the case of the other aspects (adaptiveness).